2013
DOI: 10.1103/physrevd.88.124020
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Galileons

Abstract: We study Galileon theories that emerge in ghost-free massive gravity. In particular, we focus on a sub-class of these theories where the Galileons can be completely decoupled from the tensor Lagrangian. These Galileons differ from generic ones -- they have interrelated coefficients of the cubic and quartic terms, and most importantly, a non-standard coupling to external stress-tensors, governed by the same coefficient. We show that this theory has no static stable spherically symmetric solutions that would int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(153 citation statements)
references
References 71 publications
3
150
0
Order By: Relevance
“…A related tension is that the galileon terms lead to scattering amplitudes which do not obey dispersion relations obtained from arguments about S-matrix analyticity, discussed in Appendix D.4. On the other hand, this argument relies on the existence of an S-matrix for galileons, which has been questioned recently in [589,590].…”
Section: Perturbations Around the Spherically-symmetric Backgroundmentioning
confidence: 99%
“…A related tension is that the galileon terms lead to scattering amplitudes which do not obey dispersion relations obtained from arguments about S-matrix analyticity, discussed in Appendix D.4. On the other hand, this argument relies on the existence of an S-matrix for galileons, which has been questioned recently in [589,590].…”
Section: Perturbations Around the Spherically-symmetric Backgroundmentioning
confidence: 99%
“…In the context of nonlinear massive gravity the implementation of this Vainshtein mechanism was considered for instance in [12,14,43,44]. At the nonlinear level the theory involves interactions of the form h(∂ 2χ ) n+1 /Λ 3n 3 , which implies that the theory is strongly coupled at the scale Λ 3 [8,27].…”
Section: Jhep04(2016)188mentioning
confidence: 99%
“…It has been shown that homogeneous and isotropic cosmological solutions, as well as static, spherically symmetric black holes, in ghost-free massive gravity are absent/unstable [43,44,48], and it has been argued that the "natural" cosmological solutions in ghost-free massive gravity are inhomogeneous/anisotropic and the "natural" black hole solutions are non-static/spherically symmetric, the deviations from the exact symmetries being typically of O(m 2 ). In the Λ 2 decoupling limit, we are forced to break Lorentz symmetries in order to have stable backgrounds, and indeed we expect that it is the Λ 2 decoupling limit that is the most appropriate description of the generic inhomogenous cosmologies in massive gravity.…”
Section: Jhep04(2016)188mentioning
confidence: 99%
“…This problem can be avoided if the non-abelian flavor symmetry is gauged, giving mass to the Goldstone modes. 1 Anomaly cancellation in such a theory requires introduction of exotic fermions [10][11][12][13][14][15] to cancel gauge anomalies. These mix with the SM fermions.…”
Section: Introductionmentioning
confidence: 99%